FREE SHIPPING AND CUSTOMER REVIEWS AS DETERMINANTS OF SHOPEE CONSUMER PURCHASE DECISIONS AMONG UNM MANAGEMENT STUDENTS - Keyzhia Ruff; Uhud Darmawan Natsir; Rahmat Riwayat Abadi; Muhammad Ichwan Musa; Isma Azis Riu (Jurnal Manajemen, 2026)
Abstract: This study aims to analyze the influence of the free shipping feature and customer reviews on purchasing decisions on the Shopee platform. This study uses a quantitative approach with an associative design. The population in this study were active students of the Management Study Program at Makassar State University, with a sample of 95 respondents determined using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS. The results showed that the free shipping feature has a positive and significant effect on purchasing decisions, meaning that the more attractive the free shipping feature offered, the higher the tendency of students to make purchases on Shopee. Customer reviews also have a positive and significant effect on purchasing decisions, so that informative and credible customer reviews can increase consumer confidence before purchasing a product. Simultaneously, the free shipping feature and customer reviews have a significant effect on purchasing decisions. The coefficient of determination value shows that both variables are able to explain purchasing decisions by 49.7%, while the remainder is influenced by other factors outside the research model. These findings confirm that consumer purchasing decisions on e-commerce platforms are not only influenced by economic incentives, but also by social information that builds trust. This research provides implications that marketplace managers and sellers need to optimize free shipping promotions and maintain the quality of customer reviews to improve consumer purchasing decisions.Keywords: Customer Review; E-Commerce; Free Shipping Feature; Purchase Decision; Shopee.